Controls on organic matter enrichment and reservoir heterogeneity in lacustrine shales: insights from the Songliao Basin, NE China - Xiaoping Mao; Xiaoping Mao; Xiurong Chen; Yongwei Yang; Qiugen Zheng (Frontiers in Earth Science)
The classic theory posits that deep-water environments (e.g., deep/semi-deep lakes in basin centers), are more conducive to the development of high-quality hydrocarbon sources. However, recent exploration efforts in shale oil and gas have revealed that organic-rich shales are more prevalent at the edges of lacustrine basins, whereas the central areas of these basins tend to be lacking in organic matter. Therefore, it is essential to conduct a thorough analysis of the distribution patterns of lacustrine shale reservoirs. This study employs analogical reasoning to compare the formation conditions of lacustrine source rocks and coal. By examining primary productivity, carbon burial rate (CBR), and fossil preservation in lacustrine systems, six lines of evidence are presented to support the assertion that black shale is more likely to form in shallow, restricted lacustrine environments. The findings indicate that shale oil and gas share similar mineralization patterns with coal; they maintain a symbiotic relationship with coal and evaporite in shallow lacustrine settings, where the CBR is significantly greater than in deep water environments. The study concludes that organic-rich shale deposits predominantly accumulate in closed to semi-closed environments, such as shallow lake bays and interbay areas, which is a critical factor contributing to the lateral heterogeneity of lacustrine shale. The condensed section during the maximum flooding stage of the lake is characterized by an organic-poor interval. It is proposed that organic matter in lacustrine shales is enriched in shallow, landward, closed, and cold depositional environments. This conclusion has been verified through the example of the Songliao Basin, indicating its universal applicability and serving as guidance for lacustrine shale oil and gas exploration.